Characterization of single nucleotide polymorphisms in chloroplast genomes of Musaceae Juss. - Bao Ngoc Mach; Hoang Dang Khoa Do (CTU Journal of Innovation and Sustainable Development)
Musaceae Juss., also called the bananas and plantains family contains essential food crops with critical economic value and nutritional and medicinal properties. In this study, complete chloroplast genomes of 55 species of Musaceae, including all three genera of Musa, Musella, and Ensete, were used to characterize single nucleotide polymorphisms. Also, nucleotide diversity among surveyed species was observed. The results showed regions of high genetic variability in the chloroplast genome and genes carrying multiple single-nucleotide polymorphisms specific for species and genera, such as ycf1, ycf2, ndhF, matK, accD, infA, and petL. A biased nucleotide conversion toward G, C, and T suggests a trend in the evolution of the Musaceae chloroplast genomes. Phylogenetic analysis revealed a close relationship between Ensete and Musella genera and confirmed the existence of two clades in the genus Musa. This study summarizes nucleotide diversity, focusing on single-nucleotide polymorphisms, which are helpful for further studies on population genetics and developing molecular markers in Musaceae.